Detection of Enterobius vermicularis in archived formalin-fixed paraffin-embedded (FFPE) appendectomy blocks: It's potential to compare genetic variations based on mitochondrial DNA (cox1) gene. - Maryam Haghshenas; Mona Koosha; Alireza Latifi; Elham Kazemirad; Arash Dehghan; Bahram Nikmanesh; Gholamreza Mowlavi (PLoS ONE, 2023)
Acute appendicitis represents one of the most common causes of emergency abdominal surgery worldwide. Meanwhile, Enterobius vermicularis has been suggested as one of the probable causes of appendicitis. In this study, the morphological characteristics of the remnant pinworms and pathologic changes were explored in old-archived FFPE tissues of appendectomies. Moreover, we provide the first molecular identification, genetic, and haplotype variation of this nematode from the old-archived FFPE tissue section of appendectomy using the mitochondrial cytochrome c oxidase subunit 1 (cox1) gene. Seventeen FFPE appendectomies with E. vermicularis infection, stored over 12-22 years, were collected from two different geographical areas of Iran. In the histopathological examination, tissue changes were observed in thirteen cases (76.4%) and inflammation in four blocks (23.5%). After DNA extraction, the cox1 gene was amplified in twelve (70.6%) cases using the nested polymerase chain reaction (PCR). Phylogenetic analysis and a median-joining network of 78 available cox1 sequences of E. vermicularis revealed 59 haplotypes. We identified five haplotypes that fell into type B. All Haplotypes are novel except for two haplotypes, Hap32 and Hap37, identical to E. vermicularis sequences from Iran, Greece, and Germany. The ranges of diversity distance and haplotype diversity within the isolates were 0-1.9% and HD:0.643-0.667, subsequently. Overall, the absence of inflammation or even tissue changes in some sections can suggest the possible non-inflammatory role of E. vermicularis in appendicitis. Although FFPE material suffers from PCR inhibition, we could successfully use nested PCR to characterize E. vermicularis in old-archived appendectomy blocks and suggest this method as a complementary diagnosis technique in pathology. While the predominant type was B in the Middle East and Europe, further studies on a larger sample size from different geographical regions could probably confirm the results obtained in the present study.